In vitro bioactivities and simulated gastrointestinal digestion studies on Guras-based traditional fermented drinks collected from Singalila ridge of the Himalayas - Majumder, Soumya; Ghosh, Arindam; Bhattacharya, Malay (jurnal1, 2023)
Guras or Rhododendron wine and its distilled form (Raksi) are popular traditional and therapeutic drinks served in the Rhododendron growing regions of the Himalayas, mainly in the northern and northeastern part of India, Nepal and Indo-Nepal Singalila ridge. In this research, lali Guras (Rhododendron arboreum Sm.) based traditional beverages such as unfermented decoction (as control), fermented Guras wine and distilled spirit Guras ko Raksi were collected from Singalila ridge of the Himalayas for analysis. In vitro experiments such as physicochemical and qualitative and quantitative biochemical tests; antioxidant assays (DPPH and iodometric assay); antibacterial assay; and simulated gastrointestinal digestion were carried out. Phytochemically rich unfermented decoction exhibited the best results in total phenolic content assay (82.18±1.13 mg/100 mL gallic acid equivalent) and fatty acid quantification (1.86±0.08%) test while the wine was found to be the most potential sample in all bioactivity tests. The wine was found to contain high amounts of glycoside and fermented distilled liquor Guras Raksi showed high presence of glycerol. Both the fermented samples exhibited high rate of digestion in simulated human digestion system compared to the phenolic rich unfermented decoction. This research validated the therapeutic potential of these Guras-based beverages in high-altitude conditions like Singalila by focusing on their biochemistry.